2021
DOI: 10.1016/j.virusres.2020.198205
|View full text |Cite
|
Sign up to set email alerts
|

The role of circular RNAs in viral infection and related diseases

Abstract: Highlights CircRNAs are formed by pre-mRNA through “back-splicing”. CircRNAs regulate host immune response and virus replication. CircRNAs have potential as diagnostic markers or treatment targets for viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 90 publications
0
24
0
Order By: Relevance
“…circRNAs were originally thought to be by-products of aberrant splicing with little functional potential [10]. Novel bioinformatic approaches coupled with biochemical enrichment strategies and deep sequencing have enabled comprehensive studies of circRNAs to be performed [9], and several studies have addressed the identi cation, characterization, and function of circRNAs during viral infection [32]. For example, human cytomegalovirus (HCMV) could cause signi cant changes in host circRNAs and it was found that circSP100 potentially bound to 10 HCMVencoding proteins, which further in uenced the process of HCMV infection [8].…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs were originally thought to be by-products of aberrant splicing with little functional potential [10]. Novel bioinformatic approaches coupled with biochemical enrichment strategies and deep sequencing have enabled comprehensive studies of circRNAs to be performed [9], and several studies have addressed the identi cation, characterization, and function of circRNAs during viral infection [32]. For example, human cytomegalovirus (HCMV) could cause signi cant changes in host circRNAs and it was found that circSP100 potentially bound to 10 HCMVencoding proteins, which further in uenced the process of HCMV infection [8].…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs were originally thought to be by-products of aberrant splicing with little functional potential [ 10 ]. Novel bioinformatic approaches coupled with biochemical enrichment strategies and deep sequencing have enabled comprehensive studies of circRNAs to be performed [ 9 ], and several studies have addressed the identification, characterization, and function of circRNAs during viral infection [ 33 ]. For example, human cytomegalovirus (HCMV) infection causes significant changes in host circRNA expression, and it was found that circSP100 potentially bound to 10 HCMV-encoding proteins, which further influenced the process of HCMV infection [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-27b-3p in DF-1 cells increases the expression of chicken IFN-β, IRF3, and NF-κB by directly binding to SOCS3/6, preventing IBDV replication in host cells. Suppression of endogenous miR-27b-3p through its inhibitors suppresses IFN-β, IRF3, and NF-κB, leading to increased expression of SOCS3/6 and increased replication of IBDV [ 34 ].…”
Section: The Role Of Mirnas In Viral Infectionmentioning
confidence: 99%